Rasionalitas Penggunaan Obat Antihipertensi Pasien Jantung Koroner Instalasi Rawat Jalan Rumah Sakit Nirmala Suri - Anom Parmadi; Sri Rejeki; Adilla Fitria Wulandari (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
Antihypertensive drugs for coronary heart disease patients require proper treatment and attention to avoid becoming a major medical issue, given the relatively high incidence rate. A risk factor for coronary heart disease is a history of hypertension. Rational evaluation of antihypertensive drug use aims to ensure appropriate medication for coronary heart disease patients. Rationality criteria for drug use include proper indication, drug selection, dosage, and patient suitability. This study aims to evaluate the rationality of antihypertensive drug use in coronary heart disease patients at the Outpatient Clinic of Nirmala Suri Hospital. The research adopts a non-experimental, descriptive analytical design with a retrospective study approach involving coronary heart disease patients from December 2020 to February 2021. Simple random sampling technique was used, and 85 samples were obtained. The research instrument was a checklist. The evaluation results of antihypertensive drug use in coronary heart disease patients at the Outpatient Clinic of Nirmala Suri Hospital from December 2020 to February 2021, based on JNC VIII guidelines and the standard guidelines of the Indonesian Ministry of Health, show rationality with percentages of 100% for patient suitability, indication, and drug selection, and 90.59% for proper dosage.